Half of a forest bird community infected with haemosporidian parasites - Strehmann, Finja; Becker, Marcel; Lindner, Kim; Masello, Juan F.; Quillfeldt, Petra; Schumm, Yvonne R.; Farwig, Nina; Schabo, Dana G.; Rösner, Sascha (Frontiers in Ecology and Evolution, 2023)
Parasites play important roles in ecosystems. Through their interactions with host and vector species, they are capable of changing the behavior and population dynamics of their host species, and the shape of entire communities. Over the past years, many studies have acknowledged the role of parasitism for host populations and communities and discovered their important regulatory functions for many vertebrate populations. Although birds are a well-studied group of vertebrates, the infection patterns of endoparasites at the community level are not fully understood. Some bird species and families are known to have a higher susceptibility to certain endoparasites than others, which may be driven by their abundance in the community. Over the course of four consecutive breeding seasons (2019–2022), we monitored the patterns of endoparasite infections in a bird community of a temperate forest ecosystem. We sampled 483 birds belonging to 29 Palearctic species and investigated the prevalence of blood parasites (haemosporidian parasites) and Trichomonas spp. using molecular methods. We found an overall prevalence of 48.1% of haemosporidians belonging to 53 genetic lineages of the three genera Haemoproteus, Leucocytozoon, and Plasmodium spp. While the bird families Turdidae (94%) and Paridae (76%) showed a high prevalence of haemosporidians, Certhiidae and Picidae were not infected (0%). Host-parasite network analysis detected high variability in interactions. We found that the prevalence and lineage diversity of haemosporidian parasites differed between avian families and that the parasite prevalence of a family could not serve as a predictor of lineage diversity. Infections with Trichomonas spp. were not observed in the forest bird community. To further assess the consequences of these host-parasite interactions for bird communities, future research should aim to disentangle the infection pathways in different ecosystems while also considering the vector community and environmental factors.